Oliver twist: treetops classics - Dickens, Charles; McCaughrean, Geraldine (Oxford University Press London, 2001)
Given a fresh look, this title features different cover logos. It provides dedicated teaching support, a Guided Reading card, and notes on the inside back covers to assist parents and teaching assistants.